2021
DOI: 10.1007/s40516-021-00161-3
|View full text |Cite
|
Sign up to set email alerts
|

Parameters Development for Optimum Deposition Rate in Laser DMD of Stainless Steel EN X3CrNiMo13-4

Abstract: Laser Direct Metal Deposition (DMD) has been developed as a manufacturing process to deposit coatings on existing materials and proves advantageous in Additive Manufacturing (AM) of complex and precise components. However, it is necessary to carefully determine the proper process parameter combinations to make this method economically viable for industries. The intent of this study is to address enhancement in productivity of laser DMD of stainless steel EN X3CrNiMo13-4. Accordingly, the effects of the main la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…This conclusion is supported by similar research [41], which found the dilution proportion c2 increases inversely when compared to the powder delivery per unit length. Additional research showed the possible instability due to excess power feed rate which leads to poor overlapping [42]; track 7 and 10 highlight this problem, as their wettability angles are both greater than 90 • .…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is supported by similar research [41], which found the dilution proportion c2 increases inversely when compared to the powder delivery per unit length. Additional research showed the possible instability due to excess power feed rate which leads to poor overlapping [42]; track 7 and 10 highlight this problem, as their wettability angles are both greater than 90 • .…”
Section: Discussionmentioning
confidence: 99%
“…The workflow only shows a section of process steps. The 2D parameter study was provided by Dalaee et al [15], and the post processing, microstructure evolution, and mechanical properties will be evaluated in further research.…”
Section: Proposed Workflow For Dmd and Laser Weldingmentioning
confidence: 99%
“…The process parameters of single tracks were determined by Dalaee et al [15]. The tool path is characterized by a closed tool path with the same start and ending point of the laser to lower the impact of the energy peaks by switching the laser on and off.…”
Section: Geometrical Parameter Studymentioning
confidence: 99%
“…Horretarako, prozesu mota honetan eragin handiena duten laserraren potentzia (P), hauts emaria (Q) eta pitaren aitzinapen abiadura (F) optimizatzea beharrezkoa da. Kordoiaren forma-parametroarentzat, bibliografian 1/5 eta 1/3 arteko balioak gomendatzen dira, honen itxura-erlazioa egokia izan dadin eta hauek gainjartzerako orduan lotura guneetan fusio-arazoak ager ez daitezen [5]. Bestalde, diluzio-parametroak oinarriaren urtzera bideratutako energia kuantifikatzen du eta kordoi ezberdinen arteko loturarekin ere zerikusia dauka.…”
Section: Metodologiaunclassified
“…Irudia (c) kasua), lotura urria izan daitekeelako. Hori dela eta, zenbait egilek, diluzio optimoa % 10 eta % 30 bitartean dagoela ondorioztatu dute [5]. Mekanizazio prozesu honetan lehenengo probeta arbastatu da, trakzio probetaren itsura hartu arte.…”
Section: Metodologiaunclassified